EVALUATION OF PROTECTIVE ANTIBODY LEVELS IN LAYING HENS FOLLOWING VACCINATION AGAINST AVIAN INFLUENZA, INFECTIOUS BRONCHITIS, AND NEWCASTLE DISEASE - Pertiwi, Vindo Rossy; Habsari, Intan Kamilia; Putri, Naimah; Usman, Nurul Azizah; Putri, Dwi Desmiyeni; Silaen, Otto Sahat Martua; Sinaga, Desi Maria; Patria, Cintia Agustin; Candra, Agung Adi; Mubarohadi, Rio; Juliawan, Kadek Rizky; Karima, Fadhila Nurul (Buletin Veteriner Udayana, 2026)
Avian Influenza (AI), Infectious Bronchitis (IB), and Newcastle Disease (ND) often infect broilers and layers. This study aimed to identify the immunological response of laying hens following vaccination against AI, IB, and ND. Laying hens received a multivalent vaccine containing AI, IB, and ND antigens at 18 and 45 weeks of age. Subsequently, antibody titers were assessed as a measure of the post-vaccination response. Blood samples were collected on days 7, 14, and 21 post – vaccination. Blood samples were collected from the brachial vein of laying hens that had been previously vaccinated. Data will be analyzed descriptively, and comparisons will be made in accordance with existing literature. The variables examined included AI, IB, and ND antibody titers. Results from the hemagglutination inhibition (HI) test for ND and AI antibodies demonstrated a notable increase in titers over the observation period. At day 0, the mean antibody titers for ND and AI were 2.5 and 4.6, respectively, suggesting that baseline antibody levels prior to the post-vaccination immune response were optimal. The ELISA IB test results were seropositive in all samples, both before and 21 days after vaccination. This indicates that all chickens already had antibodies against the IB virus. The study concluded that the highest protective antibody titers for AI, ND, and IB vaccines occurred between days 14 and 21 for AI and IB. Meanwhile, for ND, a decline in protection is observed after day 14, attributable to several factors including vaccine efficacy not guaranteeing complete protection, the timing of administration, the vaccine dose and route of administration, human error (particularly with injectable routes), and the specific strain used. Implementing biosecurity measures within poultry houses is crucial to prevent ND transmission.